Characteristics of serum lipid levels in patients with hypertension: a hospital-based retrospective descriptive study - Heming Wu; Zhikang Yu; Qingyan Huang (BMJ Open)
Background Dyslipidaemia is different among patients with hypertension in different populations. The serum lipid profiles among Hakka patients with hypertension in southern China are still unclear.Methods 35 448 patients with hypertension were enrolled in this study from January 2016 to October 2020, and their serum lipids were analysed.Results Low high-density lipoprotein-cholesterol (HDL-C) (29.9%) accounted for the highest proportion in dyslipidaemia, followed by high triglyceride (TG) (20.7%), high total cholesterol (TC) (14.0%) and high low-density lipoprotein-cholesterol (LDL-C) (7.9%) in all subjects. The largest proportion of dyslipidaemia types was independent low HDL-C (12.7%). The proportion of low HDL-C was 15.5% in non-elderly men, 6.4% in non-elderly women, 16.7% in elderly men and 8.5% in elderly women, respectively. The largest proportion of dyslipidaemia types was independent high TG in non-elderly female patients (13.7%) and elderly patients (8.9%). The results showed that higher LDL-C, TC and TG levels in non-elderly patients than elderly patients. TG, TC and LDL-C levels decreasing with the increasing age, the differences were statistically significant. The levels of TG, TC, HDL-C and LDL-C in women were higher than in men among various age groups. Homocysteine level was increasing with increasing age.Conclusions Serum lipid levels varied in different groups according to age and sex in patients with hypertension. Dyslipidaemia is more common in non-elderly patients than elderly. TG, TC and LDL-C levels were higher in female patients than male.